(untitled) (Journal of Enam Medical College, 2014)
Background: Diabetic retinopathy is a vascular disorder affecting the microvasculature of retina. It is caused by changes in the blood vessels of retina. If untreated, it may lead to blindness which is usually preventable if retinopathy is diagnosed early and treated promptly. In ophthalmology, color Doppler imaging is a new method that enables us to assess the orbital vasculature. It allows for simultaneous two dimensional anatomical and Doppler evaluations of hemodynamic characteristics of retinal artery. Objective: To observe the difference between Doppler flow velocity indices (peak systolic velocity, end diastolic velocity and resistive index) of retinal artery in type 2 diabetic subjects without retinopathy and those of normal controls. Materials and Methods: This case-control study was carried out in the department of Radiology and Imaging, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) in collaboration with Ophthalmology Outpatient Department, BIRDEM, Dhaka from July 2011 to June 2013. Eighty diabetic patients without retinopathy aged 2768 years were enrolled as cases and age and sex matched 80 healthy subjects were selected as controls. Type 1 diabetic patients, type 2 diabetics with retinopathy, hypertensive and dyslipidemic subjects were excluded from the study. All the selected subjects underwent duplex Doppler ultrasonography of both eyes using 5 to 7.5 MHZ linear phase transducer. Duplex color Doppler findings including spectral analysis (PSV, EDV and RI) were recorded. Unpaired t test was done to compare blood flow velocity indices of retinal artery in type 2 diabetic patients without retinopathy and that of healthy control subjects. p value <0.05 was considered as significant. Results: Majority (42.5% and 47.5%) of subjects were in 4th decade of life in both groups with predominance of males. The mean duration of diabetes was 4.56 ± 2.1 years. Mean peak systolic velocity (PSV) in 80 diabetic patients without retinopathy was 10.70 ± 1.50 cm/sec ranging 5.3016.10 cm/sec and that of 80 healthy subjects was 11.27 ± 0.98 cm/sec ranging 9.013.10 cm/sec. Mean end diastolic velocity (EDV) in 80 diabetic patients without retinopathy was 2.58 ± 0.67 cm/sec ranging 1.00 5.10 cm/sec and that of 80 healthy subjects was 4.11 ± 2.7 cm/sec ranging 3.004.60 cm/sec. Mean resistive index (RI) in 80 diabetic patients without retinopathy was 0.75 ± 0.04 ranging 0.660.81 and that of 80 healthy subjects was 0.64 ± 0.02 ranging 0.600.70. Mean difference of retinal arterial RI of diabetic subjects without retinopathy and healthy control eyes was statistically significant (p<0.001). Conclusion: From the present study it can be concluded that, there is statistically significant difference between retinal arterial RI of type 2 diabetic patients without retinopathy and that of healthy control adult subjects. DOI: http://dx.doi.org/10.3329/jemc.v4i3.20948 J Enam Med Col 2014; 4(3): 168-173